088. Transarterial Chemoembolization for Head and Neck Cancer: Case Series - Sembiring, Samuel Pola Karta; Rizki, Kiki Akhmad (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Head and neck cancers represent a diverse group of malignancies arising from the complex anatomy of the oral cavity, pharynx, larynx, nasal cavity, paranasal sinuses, and salivary glands. While traditional treatments like surgery, radiation, and chemotherapy remain mainstays, transarterial chemoembolization (TACE) has emerged as a potential therapeutic option, particularly for advanced or recurrent cases. We present two cases of head and neck cancer that receive TACE. Case : First Case: A 46 years old woman, with big lump on her left cheek. The patient was diagnosed with Basal Cell Adenocarcinoma T3N0M0 at right submandibular region. He has history of Docetaxel and Carboplatin 6 cycles chemotherapy. Second Case: A 51 years old man, complain a lump on his right tongue. The patient was diagnosed with Squamous Cell Carcinoma Well Differentiated at left glossus region. But no history of chemotherapy. Conclusion : Two cases with head and neck cancer in our center has good clinical outcome after receiving chemotherapy through TACE procedure. TACE is offering a targeted approach to deliver chemotherapy and induce tumor necrosis. Although, TACE is commonly used for liver cancer, but it demonstrates promising potential in improving outcomes for head and neck cancer patients in the future.